2010
DOI: 10.1135/cccc2009098
|View full text |Cite
|
Sign up to set email alerts
|

A modified Poisson–Boltzmann study of the singlet ion distribution at contact with the electrode for a planar electric double layer

Abstract: The properties of the singlet ion distributions at and around contact in a restricted primitive model double layer are characterized in the modified Poisson-Boltzmann theory. Comparisons are made with the corresponding exact Monte Carlo simulation data, the results from the Gouy-ChapmanStern theory coupled to an exclusion volume term, and the mean spherical approximation. Particular emphasis is given to the behaviour of the theoretical predictions in relation to the contact value theorem involving the charge p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The MPB theory does not satisfy exactly the contact condition [60][61][62] which holds for no imaging. Previous work [63][64][65] has shown that the MPB5 theory fairly accurately satisfies the contact condition for 1:1 electrolytes and gives a good agreement for 1:2/2:1 and 2:2 electrolytes. A similar conclusion holds in general when the new F is used, but the MPB4 theory can be poor.…”
Section: Discussionmentioning
confidence: 84%
“…The MPB theory does not satisfy exactly the contact condition [60][61][62] which holds for no imaging. Previous work [63][64][65] has shown that the MPB5 theory fairly accurately satisfies the contact condition for 1:1 electrolytes and gives a good agreement for 1:2/2:1 and 2:2 electrolytes. A similar conclusion holds in general when the new F is used, but the MPB4 theory can be poor.…”
Section: Discussionmentioning
confidence: 84%
“…The MC data is again well described by Equation (17). Figure 9 shows an overall view of the changing pattern of asymmetry in the double layer through the plots of MC g diff ðct, bÞ, the GCS (or the PB) g diff ðct, bÞ, and the HB relation [Equation (17)]. Although some of the individual results have been observed in previous publications [12,21,22], it is revealing to have a global view.…”
Section: Resultsmentioning
confidence: 71%
“…The essential behaviour of the results follow the earlier patterns in Figures 1-4, although perhaps slightly less pronounced because of the lower densities. The MC data is again well described by Equation (17). Figure 9 shows an overall view of the changing pattern of asymmetry in the double layer through the plots of MC g diff ðct, bÞ, the GCS (or the PB) g diff ðct, bÞ, and the HB relation [Equation (17)].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations